Unravel: the power and politics of textiles in art - Fray-Smith, Wells; Johnson, Lotte ca. 20. Jh; Pinatih, Amanda 1987- (Prestel Verlag in association with Barbican Art Gallery and Stedelijk Museum Amsterdam, 2024)
The transformative power of contemporary textiles is the subject of this exhibition catalog that examines how and why textile has been a fertile medium for artists to question regimes of power and hierarchies of value. Bringing together more than 100 works by a diverse range of international practitioners, this eye-opening volume explores how textile art can be as discomforting as it is beautiful, and how age-old materials and processes are being reimagined with boundary-smashing innovations. From intimate hand-crafted works to large-scale sculptural installations, this book celebrates the legacies of artists such as Pacita Abad, the arpilleristas, and José Leonilson. Also featured here are works by living artists such as Igshaan Adams, Tracey Emin, and Cecilia Vicuña. Featuring new essays by Julia Bryan-Wilson, Miguel A. Lopez and Denise Ferriera da Silva, and texts by Michelle Adler, Diego Chocano, Wells Fray-Smith, Lotte Johnson and Amanda Pinatih, this beautifully produced book features a collection of renowned artists from around the world and reveals the extraordinary potential of textiles to confront fixed notions of history, race, gender, sexual expressions, and class—and how, ultimately, it can be a powerful force for both resistance and repair.
Haupttitel dem Buchrücken entnommen
Titel auf Haupttitelseite spiralförmig von oben nach unten: Unravel unravel unravel unravel unravel unravel unravel
Aus dem Impressum: "First published in 2024 [...] on the occasion of the exhibition 'Unravel: the power and politics of textiles in art'; Barbican Art Gallery, 13 February - 26 May 2024; Stedelijk Museum Amsterdam, 14 September 2024 - 5 January 2025"
Participating artists: Pacita Abad (The Philippines/USA), Magdalena Abakanowicz (Poland), Igshaan Adams (South Africa), Ghada Amer (Egypt/France), Arpilleristas (Chile), Mercedes Azpilicueta (Argentina), Yto Barrada (Morocco), Kevin Beasley (USA), Sanford Biggers (USA), Louise Bourgeois (France / USA), Diedrick Brackens (USA), Jagoda Buić (Croatia), Margarita Cabrera (Mexico / USA), Feliciano Centurión (Paraguay), Judy Chicago (USA), Myrlande Constant (Haiti), Cian Dayrit (The Philippines), Tracey Emin (UK), Jeffrey Gibson (USA), Antonio Jose Guzman and Iva Jankovic (The Netherlands / Panama and The Netherlands / Yugoslavia), Harmony Hammond (USA), Sheila Hicks (USA), Nicholas Hlobo (South Africa), Yee I-Lann (Malaysia), Kimsooja (South Korea), Acaye Kerunen (Uganda), José Leonilson (Brazil), Tau Lewis (Canada), Ibrahim Mahama (Ghana), Teresa Margolles (Mexico), Georgina Maxim (Zimbabwe), Małgorzata Mirga-Tas (Poland), Mrinalini Mukherjee (India), Violeta Parra (Chile), Solange Pessoa (Brazil), Loretta Pettway (Gee’s Bend) (USA), Antonio Pichillá Quiacaín (Guatemala), Faith Ringgold (USA), LJ Roberts (USA), Zamthingla Ruivah (India), Hannah Ryggen (Norway), Tschabalala Self (USA), Yinka Shonibare CBE RA (UK), Mounira Al Solh (Lebanon), Angela Su (Hong Kong), Lenore Tawney (USA), T. Vinoja (Sri Lanka), Cecilia Vicuña (Chile), Billie Zangewa (Malawi / South Africa), and Sarah Zapata (Peru / USA)
Keywords: Soziales Engagement; Textilkunst; Textile crafts / Exhibitions; Fabric textiles / Exhibitions; exhibition catalogs; Exhibition catalogs; Catalogues d'exposition; Ausstellungskatalog -- Barbican Art Gallery -- 13.02.2024-26.05.2024 -- London; Ausstellungskatalog -- Stedelijk Museum Amsterdam -- 14.09.2024-05.01.2025 -- Amsterdam; Bildband